2006
DOI: 10.1111/j.1460-9568.2006.04861.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐inhibitory interactions between GABAA and P2X channels in myenteric neurones

Abstract: Inhibitory interactions between GABA(A)[induced by gamma-aminobutyric acid (GABA)] and P2X [activated by adenosine 5'-triphosphate (ATP)] receptors of myenteric neurones from the guinea pig small intestine were characterized using whole-cell recordings. Currents induced by GABA (I(GABA)) or ATP (I(ATP)) were inhibited by picrotoxin or pyridoxalphosphate-6-azophenyl-2',4'-disulphonic acid, respectively. Currents induced by GABA + ATP (I(GABA+ATP)) were only as large as the current induced by the most effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…In our current work, cross-inhibition between recombinant P2X4 and GABA A receptors was voltage-and ion-independent, which is consistent with the previous studies of other P2X subtypes and cys loop receptor members (12)(13)(14)(15)(16)(17)(18)(19)21). In addition, our biochemical and immunohistochemical experiments in transfected cells and SF-1 GFP-positive neurons further provide the cellular mechanisms that mediate cross-inhibition between the two distinct receptors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our current work, cross-inhibition between recombinant P2X4 and GABA A receptors was voltage-and ion-independent, which is consistent with the previous studies of other P2X subtypes and cys loop receptor members (12)(13)(14)(15)(16)(17)(18)(19)21). In addition, our biochemical and immunohistochemical experiments in transfected cells and SF-1 GFP-positive neurons further provide the cellular mechanisms that mediate cross-inhibition between the two distinct receptors.…”
Section: Discussionsupporting
confidence: 91%
“…ATP is released either with an inhibitory neurotransmitter, GABA 4 (7)(8)(9)(10) or with an excitatory neurotransmitter, glutamate in the CNS (4,11). Recent studies have clearly demonstrated the interactions of P2X receptors with other ligand-gated channels, including 5-hydroxytryptamine, GABA A , or nicotinic receptors in recombinant expression and cell culture preparations (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). It thus appears that P2X receptors prefer to interact with other receptors rather than act independently.…”
mentioning
confidence: 99%
“…Simultaneous activation of nicotinic and P2X receptors produces a response that is smaller in amplitude than the predicted sum of responses caused by individual activation of each receptor. Recently, GABA A currents or current produced by activation of 5-HT 3 receptors has also been found to occlude P2X currents in much the same way [71,72]. Taken together, these data suggest that a functional interaction between P2X and other ligand-gated channels may be the norm and thus physiologically important.…”
Section: Interactions Between P2x Receptors and Other Ligand-gated Iomentioning
confidence: 73%
“…GABA A Rs and P2X 2 Rs have been demonstrated to be co-localized and to functionally interact with each other in the spinal cord and dorsal root ganglion (20,21). Simultaneous activation of GABA A Rs and P2X 2 Rs results in nonadditive currents or "cross-talk" of the receptors (22,23). Similar cross-talk was also observed between P2X 2 Rs and other members of the cys-loop receptor family (24 and references therein).…”
mentioning
confidence: 81%
“…As members from the P2XR family have been demonstrated to show cross-talk with not only GABA A Rs (20,22,23,58) but also with several other members of Cys loop receptors, which includes 5-hydroxytryptamine/serotonin type 3 receptors (59, 60), GABA C receptors (54), and nicotinic acetylcholine receptors (61,62), association of P2X 2 Rs with other receptors and co-trafficking to specific locations at the cell surface in fact may be a general phenomenon. Indeed, such Cys loop receptor-mediated recruitment to the cell surface is possibly not restricted to P2X 2 Rs as several other members of P2XR family are now known to interact with GABA A Rs (P2X 1 , P2X 4 , and P2X 5 , experiments not shown; P2X 3 (20,58)) and nicotinic receptors (P2X 2 , P2X 3 , and P2X 4 (61)).…”
Section: Purinergic Transmission Decreases Gabaergic Inhibition In Spmentioning
confidence: 99%